2019
DOI: 10.1103/physrevx.9.021038
|View full text |Cite
|
Sign up to set email alerts
|

Relating Chain Conformation to the Density of States and Charge Transport in Conjugated Polymers: The Role of the β -phase in Poly(9,9-dioctylfluorene)

Abstract: Charge transport in π-conjugated polymers is characterized by a strong degree of disorder in both the energy of conjugated segments and the electronic coupling between adjacent sites. This disorder arises from variations in the structure and conformation of molecular units, as well as the weak intermolecular binding interactions. Although disorder in molecular conformation can be expected to influence the density of states (DOS) distribution-and hence, optoelectronic properties of the material-until now, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 122 publications
3
40
0
Order By: Relevance
“…Experimental determinations of the relative positions of the β-phase HOMO and LUMO levels are, however, inconclusivespectroelectrochemical hole doping of β-phase PFO samples has shown that the β-phase oxidation potential is lower than the glassyphase by ΔE ≈ 100-150 meV, 63 indicative of a shallower HOMO level; and photocurrent and impedance spectroscopies suggest that the β-phase HOMO is also shallower by ΔE ≈ 300 meV. 76 Meanwhile, trap-filling thermally stimulated current measurements exhibit no evidence of a difference in glassy and β-phase HOMO levels, but find the LUMO of the βphase to be deeper than the glassy-phase by ΔE ≈ 120 meV. 32 Given this uncertainty, in combination with the local variation in HOMO and LUMO energies of glassy-phase chains due to conformational variation, it is reasonable to speculate that within a PFO film there may be a (small) fraction of glassy/β-phase interfaces which form type II rather than type I heterojunctions, where offsets between HOMO or LUMO levels of neighbouring glassy and β-phase chain segments favour charge separation over energy transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental determinations of the relative positions of the β-phase HOMO and LUMO levels are, however, inconclusivespectroelectrochemical hole doping of β-phase PFO samples has shown that the β-phase oxidation potential is lower than the glassyphase by ΔE ≈ 100-150 meV, 63 indicative of a shallower HOMO level; and photocurrent and impedance spectroscopies suggest that the β-phase HOMO is also shallower by ΔE ≈ 300 meV. 76 Meanwhile, trap-filling thermally stimulated current measurements exhibit no evidence of a difference in glassy and β-phase HOMO levels, but find the LUMO of the βphase to be deeper than the glassy-phase by ΔE ≈ 120 meV. 32 Given this uncertainty, in combination with the local variation in HOMO and LUMO energies of glassy-phase chains due to conformational variation, it is reasonable to speculate that within a PFO film there may be a (small) fraction of glassy/β-phase interfaces which form type II rather than type I heterojunctions, where offsets between HOMO or LUMO levels of neighbouring glassy and β-phase chain segments favour charge separation over energy transfer.…”
Section: Discussionmentioning
confidence: 99%
“…We note that gpvdm has been validated against experimental data in the past. [33,63,64] Despite that for extreme low values of !,#$% FF goes down with !,#$% , within commonly observed FF values in the range from 50% to 70%, we find that FF increases with ! for both direct and trap-mediated recombination.…”
Section: A Comparison Of the Analytical And Numerical Models At 1 Sumentioning
confidence: 99%
“…[ 4–8 ] This development was mostly fueled by the use of novel, small‐molecule acceptor materials that replaced the previously used fullerene‐based acceptors and led to improved absorption and reduced nonradiative recombination losses. [ 9–15 ] Despite the substantial amount of structural and conformational disorder present in these molecular semiconductor blends, [ 16–18 ] efficiencies of organic solar cells under standardized test conditions have been improved to >18%, [ 7,8 ] that is, substantially higher than that of highly disordered inorganic solar cells such as those based on amorphous Si absorber layers. [ 3 ] In addition, applications of organic photovoltaics beyond the traditional large‐scale power generation market have become more important, both from a scientific and economic point of view.…”
Section: Introductionmentioning
confidence: 99%